Legal regulation of open databases as a key aspect of e-government - Zavada, Rostyslav (Global Prosperity, 2023)
The article analyzes the latest aspects of legal regulation of open databases as a key aspect of electronic governance. It is indicated that Ukraine’s European integration aspirations require compliance with international and regional standards in the field of legal support for the openness of databases. This is of significant importance as a factor in the renewal of public-authority relations through the use of the electronic governance system. It was established that the legal regulation of open databases is ensured at the international level and at the level of the European Community. There is a continuous process of updating the principles and approaches to ensuring the openness of public data, updating and changing regulatory and legal acts. The right of access applies to both individuals and legal entities, without discrimination, including on the basis of national origin, and even to foreigners living outside the territory of states that have ratified the normative standards. The areas of law that must have regulatory support are highlighted: legal norms that include access to information (Universal Declaration of Human Rights; Council of Europe Convention on Access to Official Documents (CETS No. 205), also known as the Tromsø Convention, which entered into force on December 1, 2020 year; national Constitutions); legal regulation of information reuse (Open Government Declaration of September 2011; Directive on Open Data and Public Sector Information Reuse 2019); legal regulation of conflicts of interest in the use of open data (Bern Convention for the Protection of Literary and Artistic Works; Directive (EU) 2019/790 of the European Parliament and the Council of April 17, 2019 on copyright and related rights in the single digital market). At the same time, within these spheres, provision is made through the level division of normative legal acts: international, regional (European), constitutional, legislative and municipal.